Optimization of Mobile SIM in Improving Public Services by the Unit Regident Traffic Police Garut Police - Putra, Muh. Evan Rafli Batara (Police Studies Review, 2021)
This research is motivated by the high number of prosecution of traffic violations without a SIM by the Traffic Police of Garut Police. One form of innovation to improve public services has been implemented by the Garut Police Traffic Police Regident Unit through the implementation of Mobile SIM to facilitate remote communities who are constrained by distance problems to extend SIM. However, the implementation is not in accordance with the main purpose of the innovation being made. Therefore, a research was conducted which aims to describe the implementation of mobile SIM in improving public services by the Regident Unit of the Traffic Police of Garut Police, the efforts of the Regident Unit in optimizing these innovations, as well as the factors that influence it. This research was conducted with a qualitative approach that focuses on optimizing mobile SIM located in Garut Regency, data collection techniques by interviewing, observing and reviewing documents, data validity using data triangulation with primary and secondary data sources and data analysis techniques in the form of data reduction, presentation. data, and drawing conclusions. The results of the study found that the optimization of mobile driving licenses in improving public services by the Garut Police Traffic Police Regident Unit analyzed by management theory and Article 21 of Law Number 25 of 2009 were appropriate to be implemented at the Garut Police. The implementation of a mobile SIM is quite good with the fulfillment of the indicators contained in Article 21 of Law Number 25 of 2009. However, there are still obstacles in terms of waiting room facilities, costing, and guaranteed service certainty, especially in determining the schedule for reaching the region. remote areas of Garut Regency. Analysis of the efforts of the Regident Unit in optimizing the mobile SIM has been going well, but it needs to be improved in the function of supervision and organization. Meanwhile, the most influential factors are market factors related to SIM extension applicants (public demand) and road infrastructure. Based on the results of the research, the researchers suggest a comprehensive outreach to the public through various media and cooperation with cellular operators, proposing education and training for SIM examiner certification for mobile SIM officers, increasing supervision and coordination in the Garut Police Traffic Police Regident Unit in order to achieve public satisfaction.